Sensitive and Reversible Detection of Methanol and Water Vapor by In Situ Electrochemically Grown CuBTC MOFs on Interdigitated Electrodes. Issue 29 (8th June 2017) - Sachdeva, Sumit; Venkatesh, Manjunath R.; Mansouri, Brahim El; Wei, Jia; Bossche, Andre; Kapteijn, Freek; Zhang, Guo Qi; Gascon, Jorge; de Smet, Louis C. P. M.; Sudhölter, Ernst J. R.
Abstract : The in situ electrochemical growth of Cu benzene‐1, 3, 5‐tricarboxylate (CuBTC) metal–organic frameworks, as an affinity layer, directly on custom‐fabricated Cu interdigitated electrodes (IDEs) is described, acting as a transducer. Crystalline 5–7 µm thick CuBTC layers are grown on IDEs consisting of 100 electrodes with a width and a gap of both 50 µm and a height of 6–8 µm. These capacitive sensors are exposed to methanol and water vapor at 30 °C. The affinities show to be completely reversible with higher affinity toward water compared to methanol. For exposure to 1000 ppm methanol, a fast response is observed with a capacitance change of 5.57 pF at equilibrium. The capacitance increases in time followed diffusion‐controlled kinetics ( k = 2.9 mmol s −0.5 g −1 CuBTC ). The observed capacitance change with methanol concentration follows a Langmuir adsorption isotherm, with a value for the equilibrium affinity K e = 174.8 bar −1 . A volume fraction f MeOH = 0.038 is occupied upon exposure to 1000 ppm of methanol. The thin CuBTC affinity layer on the Cu‐IDEs shows fast, reversible, and sensitive responses to methanol and water vapor, enabling quantitative detection in the range of 100–8000 ppm. Abstract : The in situ electrochemical growth of Cu benzene‐1, 3, 5‐tricarboxylate (BTC) metal–organic frameworks directly on custom‐fabricated, microstructured Cu interdigitated electrodes is reported. The resulting CuBTC‐modified electrodes show a fast, reversible, and sensitive capacitive response to methanol and water vapors, enabling a quantitative detection in the range of 100–8000 ppm.